Does foreign aid undermine "self-reliance"? - ZERE, Redae (KDI School, 2019)
This study tests a hypothesis about the impact of foreign aid in Eritrea and whether it really achieved its intended goals. It further analyses foreign aid effectiveness and how it affects the policy of self-reliance in Eritrea. It attempts to investigate the way aid was channeled and the degree to which the country has had control of the process as well as setting the priorities which are closely related to “self-reliance”. The study seeks to answer the following questions: “Was aid delivered in a way that strengthened country ownership or undermined it? Does it undermine the policy of “self-reliance”? And how can cooperation between Eritrean government and donors be adjusted in order to better enhance ownership and “self-reliance” and overall aid effectiveness? The data for this study was collected mainly from the Ministry of National Development and the Ministry of Foreign Affairs of the State of Eritrea-two Ministries Primarily dealing with International Cooperation. Both primary and secondary data sources were used. Interviews were also conducted with 5 key top ranking government officials. In this study, it is revealed that although the government of Eritrea negotiated very well and had a strong ownership in the process of aid delivery and setting priorities, the donor’s approach especially that of EU was ‘rigid’ in the eyes of the Eritrean government and created friction at times. The study further reveals that, Eritrea, although relatively less corrupt compared with many recipient countries, it showed lack of absorption capacity as well as weak institutions that made aid less effective in some areas. Eritrean government believes that its “self-reliance” policy was misunderstood as “isolationist” and created friction at times with donors.
Thesis(Master) -- KDI School: Master of Development Policy, 2019
Keywords: Economic assistance--Eritrea